CONTROL ENGINEERING ON BOARD - Serghei RADU; GheorgheSAMOILESCU (Fiabilitate şi Durabilitate)
Control engineering embraces instrumentation, alarm systems, control of machinery and plant previously known under the misnomer of automation. Control engineering can be applied not only to propelling and auxiliary machinery but also to electrical installations, refrigeration, cargo handling (especially in tankers) and deck machinery, e.g. Windlass control. Opinion still vary on such matters as the relative merits of pneumatic versus electronic system and whether the control center should be in the engine room or adjacent to the navigating bridge. Arguments against the exclusion of the engineer officer from close contact with the machinery are countered by the fact that electronic systems are based on changes other than those of human response. Automated ships (UMS) operate closer to prescribed standards and therefore operate with greater efficiency. The closer control of machinery operating conditions, e.g. cooling water temperatures and pressures, permits machinery to be run at its optimum design conditions, making for fuel economy and reduced maintenance. Automation can carry out some tasks far more effectively than men. In other areas it is less effective. For example, the monitoring of machinery operating conditions such as the temperatures and pressures can be carried out by a solid state alarm scanning system at the rate of 400 channels/sec., giving a degree of surveillance which would be impossible by human observation. Conversely, the detection of noisy bearing, a leaky gland or cracked pipe is scarcely possible by automatic means. The balance between the possible and the necessary would be achieved in this case by combining automatic monitoring of all the likely fault conditions, with routine machinery space inspection say twice a day.